Արդահանի հարցը հայ-վրացական հարաբերություններում և խնդրի ժամանակավոր լուծումը (1919 թ. մայիս-դեկտեմբեր) - Թորոսյան, Շիրակ (YSU Journal of International Affairs, 2016)
The province of Ardahan was important for the First Republic of Armenia, as it was the only way to the Black Sea via the Black Sea neighboring areas. In April 1919, by the decision of the British occupation authorities Shura - the so-called interim government of South West Caucasian Republic was disbanded and the province of Ardahan, except for its northern part was given to Armenia (territory north of the Kura and Potskhovi site). The British allowed Georgian troops to occupy the northern part. Despite the decision of the British, the Georgians continued baseless claims to the areas of Ardahan and Olti of Kars province. From mid-April to May and until the autumn the Armenian-Georgian dispute over Ardahan continued. The withdrawal of Georgian troops from the region was largely resolved at the end of Septemberbeginning of October 1919, via the mediation of the High Commissioner of the Entente Colonel Haskell. However, as the events of 1920 showed, the Menshevik government of Georgia not only abandoned its claims to Ardahan, but also taking advantage of the Turkish-Armenian War, captured the entire Ardahan.
Keywords: Alexander Khatisyan, general Kvinitadze, Ardahan Province, Batum, Trabzon, Armenian-Georgian relations, Armenian-Georgian disagreements, Muslim population